Rancang Bangun Sistem Informasi Penjualan Dan Pembelian Alat Tulis Kantor Pada CV. Putra Mandiri - Rifky Permana; Daning Nur Sulistyowati; Ani Oktarini Sari; Tika Adilah Mutiara (Universitas Bina Sarana Informatika, 2020)
CV. Putra Mandiri which is engaged in sales of office stationery and photocopy service its’s still using manual program, begin from entry data process, save others file which is related to sale and purchasing process until sales report and purchasing report, when the process run or continue it’s enable mistake in registration or entry data. Less accurate report and long time in search file which is needed. The design program is the best solution to solve the problem in transaction service, report, work speed process and easy to get information which is anytime need. Because that, so the author try to keep with as information which is efficient and accurate, so when the sales transaction do, it’s better than past manual system